2016
DOI: 10.1002/chem.201504579
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐Ion Storage Properties of FeS–Reduced Graphene Oxide Composite Powder with a Crumpled Structure

Abstract: The sodium-ion storage properties of FeS-reduced graphene oxide (rGO) and Fe3O4 -rGO composite powders with crumpled structures have been studied. The Fe3 O4 -rGO composite powder, prepared by one-pot spray pyrolysis, could be transformed to an FeS-rGO composite powder through a simple sulfidation treatment. The mean size of the Fe3O4 nanocrystals in the Fe3O4 -rGO composite powder was 4.4 nm. After sulfidation, FeS nanocrystals of size several hundred nanometers were confined within the crumpled structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
75
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 64 publications
7
75
0
Order By: Relevance
“…As seen in Figure 2a, only limited amount of N 2 can be ad/desorbed by PB3-1S even at high pressure, while for PBC1-1S the quantity of N 2 ad/desorbed is larger, exhibiting a typical IV type isotherms. [21] The intense satellite structure (marked as sat in figure) is assumed to be a direct consequence of the band structure associated with octahedral Fe 2+ in the sulfide lattice, which allows for admixture of sulfur 2p character. The pore size distribution of PB3-1S and PBC1-1S can be seen from the inset in Figure 2a, it is found that PB3-1S hardly exhibits any porous structure, in line with the random isolated particles observed by Field Emission Scanning Electron Microscope (FESEM) (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in Figure 2a, only limited amount of N 2 can be ad/desorbed by PB3-1S even at high pressure, while for PBC1-1S the quantity of N 2 ad/desorbed is larger, exhibiting a typical IV type isotherms. [21] The intense satellite structure (marked as sat in figure) is assumed to be a direct consequence of the band structure associated with octahedral Fe 2+ in the sulfide lattice, which allows for admixture of sulfur 2p character. The pore size distribution of PB3-1S and PBC1-1S can be seen from the inset in Figure 2a, it is found that PB3-1S hardly exhibits any porous structure, in line with the random isolated particles observed by Field Emission Scanning Electron Microscope (FESEM) (Figure 1b).…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic voltammetry (CV) curves were tested to investigate the electrochemical behavior of the sulfidized products PB3-1S and PBC1-1S as anodes for SIB, as shown in Figure 3a,b. In the first cycle, the two cathodic peaks at ≈0.5 and ≈0.8 V can be ascribed to the multistep sodiation mechanism, including the sodium insertion that forms sodiated metal sulfides and the conversion mechanism forming metal and Na 2 S. [20,21] In the sodium insertion mechanism, Na + ions will be inserted into the crystal sites in the sulfides without changing the crystal structure. In the first cycle, the two cathodic peaks at ≈0.5 and ≈0.8 V can be ascribed to the multistep sodiation mechanism, including the sodium insertion that forms sodiated metal sulfides and the conversion mechanism forming metal and Na 2 S. [20,21] In the sodium insertion mechanism, Na + ions will be inserted into the crystal sites in the sulfides without changing the crystal structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The O element can be ascribed to the residual oxygen functional groups attached to the surface of rGO NSs. [32][33][34][35] The Fe 2p spectrum (Figure 3f) shows two peaks located at 708.9 and 721.4 eV, which can be ascribed to Fe 2p 3/2 and Fe 2p 1/2 of Fe 2+ , respectively. [31] The high-resolution S 2p spectrum (Figure 3e) can be fitted to four peaks located at 161.4, 162.6, 163.9, and 165.1 eV.…”
Section: Physicochemical and Structural Characteristicsmentioning
confidence: 99%
“…As shown in the C 1s spectrum (Figure 3d), CO (epoxy or alkoxy) and CO (carbonyl or carboxyl) groups have been identified and their low peak intensity confirms the successful reduction of GO. [16,27,[32][33][34][35] The first two peaks correspond to S 2− , whereas the other two centered at higher binding energy belong to S n 2− , both of which are characteristics of iron sulfides.…”
Section: Physicochemical and Structural Characteristicsmentioning
confidence: 99%